Cultural Character in the Digital Era: A SWOT Study of the Tenggerese Indigenous Community - Awaluddin Hidayat Ramli Inaku; Besse Syaharani Ziadah; Chalista Devi Lestari; Duma Putnama Gradety Sihite; Lasma Barbara Naibaho; Meliana Yosepha Hutajulu; Erwan Adi Saputro (jses, 2025)
An ethnic group is a community of people connected by similarities in race, religion, national origin, or a combination of these elements, and bound by a shared cultural value system. According to the Encyclopedia of the Indonesian Language, an ethnic group refers to a social group within a society or cultural context that holds specific meanings or positions due to lineage, customs, religion, language, and other factors. This study aims to identify the processes of interreligious harmony occurring among the Tenggerese indigenous community through their existing intellectual and social capital, and to examine the structure of social capital within the indigenous community in fostering social harmony. The research employs an analytical method with data collected through literature review and fieldwork. The findings demonstrate that the Tenggerese indigenous community preserves its local wisdom through values upheld in the process of harmonization, and that such wisdom is sustained within society largely through the influence of prevailing myths.